Integration of Local Culture in the Learning Process at Madrasah: A Sociological Analysis - Ibrahim Ibrahim; Syamsu A. Kamaruddin; Abdul Majid; Idham Idham; Abdullah Azzam Bishri; Adul Leesen (International Journal of Social Learning (IJSL), 2026)
This study is motivated by the need to preserve local cultural values within modern educational settings, particularly the Bugis–Makassar values of siri’ (self-worth), pesse (empathy), sipakatau (humanizing one another), and sipakainge’ (mutual reminder). These values are considered essential for strengthening students’ character and fostering harmonious social interaction in schools. This research aims to analyze how Bugis–Makassar cultural values are integrated into the learning process at Madrasah Aliyah Swasta Darud Da'wah Wal-Irsyad (MAS-DDI) Baru-Baru Tanga Pangkep. A qualitative approach was employed with participants including the principal, Islamic Education teachers, Guidance and Counseling teachers, Islamic Cultural History teachers, and students from grades XI and XII. Data were collected through semi-structured interviews, observations, and documentation, and validated using data triangulation. The findings reveal that cultural values are integrated into both formal and non-formal learning through contextual, collaborative, and reflective strategies. These practices contribute to character development, enhanced learning motivation, and the strengthening of students’ cultural identity.